Archaeometric Analyses of the Building Materials for the Karabük Ovacik Çukur Mosque - Murat Eroğlu; Muhammet Bilgen; Ezgin Yetiş; Yusuf Kağan Kadıoğlu; Kıymet Deniz (Art-Sanat)
This study aims to determine the conservation status of Karabük Ovacık Çukur Mosque building materials using analytical methods. Çukur Mosque is connected to the Ovacık district of Karabük and is 12 km away from the district center. The distance between Karabük and Ovacık is 48 km. Originally, the wooden roofed building consisted of a harim. Stone, mortar, rendering, and paint samples of the mosque were examined due to their architectural properties, dated to the end of the19th and beginning of the 20th century. Analytical methods were used to determine the physical, chemical, and petrographic properties of building materials, including raw material samples. The following techniques were used for performing the analysis: Silicate aggregate/binder analysis, granulometric sieve analysis-particle size distribution, X-Ray Fluorescence analysis, Confocal Raman Spectroscopy analysis, Fourier Transform Infrared Spectroscopy analysis, and petrographic examinations. Material samples were photographed, documented, and coded for laboratory studies within the scope of the study. The results showed the identification of aggregatebinder properties in mortars and renderings and cement in some samples. Conversely, various pigments of mineral origin and organic properties were identified in paints.